Effects of Slowdown in Industrial Countries on Growth in Non-Oil Developing Countries - Khan, Mohsin; Goldstein, Morris (Washington, D.C. : International Monetary Fund, 1982)
One of the more important yet puzzling aspects of the recent global stagflation has been the rather surprising resiliency of growth rates of real income in non-oil developing countries during the 1973-80 period in the face of the marked slowdown of corresponding growth rates in the industrial world. The primary purpose of this paper is to shed some light on this phenomenon by examining the relationship between the rate of economic growth in the non-oil developing countries and that in the industrial countries over the past decade or so.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet